THE CONTRIBUTION OF ENGLISH STUDENTSâ SPEAKING STRATEGIES AND MOTIVATION ON THEIR SPEAKING ABILITY AT TARBIYAH FACULTY OF IAIN IMAM BONJOL PADANG - Kustati, Martin (AT-TALIM, 2012)
Abstract: The aims of the study are to describe: 1. Speaking strategies that are most frequently used by the students of the English Department in Tarbiyah Faculty; 2. The contribution of Studentsâ Speaking-Related LLS in developing their speaking ability; and, 3. The contribution of studentsâ learning motivation in the development of their speaking skills. speaking test, strategy inventory for language learning (SILL), and learning motivation questionnaire were employed to collect the data. The research findings revealed that there were thirty-four speaking strategies which were most frequently used by high, average, and low achievement students. The findings also showed that bothe studentsâ speaking strategies and motivation give significant contribution on studentsâ speaking ability.Â  Thus, speaking lecturers are expected to be able to implement innovative and varied teaching techniques.